Early post‐operative psychosocial and weight predictors of later outcome in bariatric surgery: a systematic literature review. (March 2017) - Hindle, A.; de la Piedad Garcia, X.; Brennan, L.
Summary: This is the first systematic review to synthesize the evidence concerning early post‐operative variables predictive of later weight and psychosocial outcomes in bariatric surgery. Eight electronic databases for empirical studies were searched (1954 to 2016). Most of the 39 included studies reported solely on weight outcomes; eating and psychosocial outcomes were less common. A better early w eight loss trajectory was the most consistent predictor of more successful medium‐term weight outcome (≤24 months); however, its relationship to longer term weight loss maintenance is less certain. Early eating adaptation may be associated with later weight loss, but further research is needed. Evidence is lacking for associations between early adherence or early psychosocial variables and later outcome. In particular, the relationship between early post‐operative depression and later weight remains unclear. Little research has considered early prediction of later eating or psychosocial outcomes. Consideration of mediating or moderating relationships is lacking. The body of evidence is limited, and synthesis is hampered by heterogeneity in the type and time at which predictors and outcomes are measured and quality of statistical reporting. Further research on prospective prediction of bariatric surgery outcome is needed to guide early post‐operative intervention for those at greatest risk of poor outcomes.